Developing a Local Cultural Indicator Framework in Australia: A Case Study of the City of Whittlesea - Yue, Audrey; Khan, Rimi; Brook, Scott (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
This paper critically examines the cultural planning agenda of the City of Whittlesea, a local government municipality in Australia, and considers its impact on the region's multicultural communities. Located on the metropolitan fringe, the City is geographically one of the largest and most diverse municipalities in greater Melbourne, with more than half of the residents from non-Anglo-Celtic backgrounds. First, the paper shows how sustainability is achieved through a structure of inter-departmental collaboration as well as in a cultural planning focus on community cultural development. Next, it examines how sustainability is implemented in its policies and programs through the development of cultural citizenship. Finally, it evaluates two community events to consider the extent of cultural participation. Combining empirical data and theoretical research, this paper aims to produce a working model for developing local cultural indicators to measure the cultural participation of non-Anglo Celtic communities. Specifically, this paper hopes to establish cultural indicators with direct policy relevance for local government, and incorporate a detailed consideration of the 'use-context' of the cultural indicators in the City in order to provide a template for best practice at municipal program levels. A localized cultural indicator framework will enable robust tools of measurement to account for thick narratives of multicultural participation that can continue to enhance well-being, place making, and belonging.